“I am feeling tension in my whole body”: An experimental phenomenological study of empathy for pain - Martínez-Pernía, David; Cea, Ignacio; Troncoso, Alejandro; Blanco, Kevin; Calderón Vergara, Jorge; Baquedano, Constanza; Araya-Veliz, Claudio; Useros-Olmo, Ana; Huepe, David; Carrera, Valentina; Mack Silva, Victoria; Vergara, Mayte (Frontiers in Psychology, 2023)
Introduction Traditionally, empathy has been studied from two main perspectives: the theory-theory approach and the simulation theory approach. These theories claim that social emotions are fundamentally constituted by mind states in the brain. In contrast, classical phenomenology and recent research based on the enactive theories consider empathy as the basic process of contacting others’ emotional experiences through direct bodily perception and sensation. Objective This study aims to enrich the knowledge of the empathic experience of pain using an experimental phenomenological method. Materials and methods Implementing an experimental paradigm used in affective neuroscience, we exposed 28 healthy adults to a video of sportspersons suffering physical accidents while practicing extreme sports. Immediately after watching the video, each participant underwent a phenomenological interview to gather data on embodied, multi-layered dimensions (bodily sensations, emotions, and motivations) and temporal aspects of empathic experience. We also performed quantitative analyses of the phenomenological categories. Results Experiential access to the other person’s painful experience involves four main themes. Bodily resonance: participants felt a multiplicity of bodily, affective, and kinesthetic sensations in coordination with the sportsperson’s bodily actions. Attentional focus: some participants centered their attention more on their own personal discomfort and sensations of rejection, while others on the pain and suffering experienced by the sportspersons. Kinesthetic motivation: some participants experienced the feeling in their bodies to avoid or escape from watching the video, while others experienced the need to help the sportspersons avoid suffering any injury while practicing extreme sports. The temporality of experience: participants witnessed temporal fluctuations in their experiences, bringing intensity changes in their bodily resonance, attentional focus, and kinesthetic motivation. Finally, two experiential structures were found: one structure is self-centered empathic experience, characterized by bodily resonance, attentional focus centered on the participant’s own experience of seeing the sportsperson suffering, and self-protective kinesthetic motivation; the other structure is other-centered empathic experience, characterized by bodily resonance, attentional focus centered on the sportsperson, and prosocial kinesthetic motivation to help them. Discussion We show how phenomenological data may contribute to comprehending empathy for pain in social neuroscience. In addition, we address the phenomenological aspect of the enactive approach to the three dimensions of an embodiment of human consciousness, especially the intersubjective dimension. Also, based on our results, we suggest an extension of the enactive theory of non-interactive social experience.